Advances in pharmacological effects and mechanism of action of cinnamaldehyde - Guo, Jiageng; Yan, Shidu; Jiang, Xinya; Su, Zixia; Zhang, Fan; Xie, Jinling; Hao, Erwei; Yao, Chun (Frontiers in Pharmacology, 2024)
Cinnamaldehyde is extracted from Cinnamomum cassia and other species, providing diverse sources for varying chemical properties and therapeutic effects. Besides natural extraction, synthetic production and biotechnological methods like microbial fermentation offer scalable and sustainable alternatives. Cinnamaldehyd demonstrates a broad pharmacological range, impacting various diseases through detailed mechanisms. This review aims to encapsulate the diverse therapeutic effects of cinnamaldehyde, its molecular interactions, and its potential in clinical applications. Drawing on recent scientific studies and databases like Web of Science, PubMed, and ScienceDirect, this review outlines cinnamaldehyde's efficacy in treating inflammatory conditions, bacterial infections, cancer, diabetes, and cardiovascular and kidney diseases. It primarily operates by inhibiting the NF-κB pathway and modulating pro-inflammatory mediators, alongside disrupting bacterial cells and inducing apoptosis in cancer cells. The compound enhances metabolic health by improving glucose uptake and insulin sensitivity and offers cardiovascular protection through its anti-inflammatory and lipid-lowering effects. Additionally, it promotes autophagy in kidney disease management. Preclinical and clinical research supports its therapeutic potential, underscoring the need for further investigation into its mechanisms and safety to develop new drugs based on cinnamaldehyde.